1998
DOI: 10.1097/00000542-199810000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane and Sevoflurane Induce Vasodilation of Cerebral Vessels via ATP-sensitive K+Channel Activation 

Abstract: The vasodilation of cerebral pial vessels induced by isoflurane and sevoflurane appears to be mediated, at least in part, via activation of adenosine triphosphate-sensitive K+ channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
90
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 30 publications
9
90
1
Order By: Relevance
“…We compared eIOS responses in awake and isoflurane anaesthetized mice (figure 1). Consistent with previous studies showing that isoflurane has vasodilatory properties [43,53], we observed strong dilation of pial arterioles when isoflurane was administered at 1.8% (v/v) in oxygen (figure 1b). Although we observed that isoflurane anaesthesia suppressed the amplitude of the eIOS ( figure 1a,c), isoflurane improved the signal-to-noise of the eIOS deoxygenation signal by suppressing vasodynamic responses (figures 1a,c and 2).…”
Section: Discussionsupporting
confidence: 92%
“…We compared eIOS responses in awake and isoflurane anaesthetized mice (figure 1). Consistent with previous studies showing that isoflurane has vasodilatory properties [43,53], we observed strong dilation of pial arterioles when isoflurane was administered at 1.8% (v/v) in oxygen (figure 1b). Although we observed that isoflurane anaesthesia suppressed the amplitude of the eIOS ( figure 1a,c), isoflurane improved the signal-to-noise of the eIOS deoxygenation signal by suppressing vasodynamic responses (figures 1a,c and 2).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with several studies that suggest that activation of K ATP channels could play a prominent role in volatile anaesthesia-induced relaxation of peripheral airways [24], coronary vessels [25], and cerebral vessels [28]. In contrast, FUKUSHIMA et al [14] found that glibenclamide pretreatment did not modify the concentrationdependent relaxation produced by halothane on canine tracheal strips incubated with indomethacin and precontracted with acetylcholine.…”
Section: Discussionsupporting
confidence: 91%
“…The anaesthetic concentrations, as well as the O 2 and CO 2 concentrations, were controlled just before entering the organ baths by the infrared absorption technique (Capnomac Datex; Ohmeda) and adjusted as needed. The bubbling was set at a relatively high rate (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) …”
Section: Volatile Anaesthetic Delivery To the Tissue Preparationmentioning
confidence: 99%
“…But, glibenclamide reduced the sevoflurane induced relaxations, implying that K ATP channels may play an important role in the relaxant effects of sevoflurane. This is consistent with the findings of Iida et al, who reported K ATP channels are involved in the vasorelaxant effects of sevoflurane and isoflurane in dog cerebral arteries (13). However, a previous study has shown that sevoflurane exerts a cardioprotective effect that is mediate via activation of K ATP channels in ischemic canine hearts (14).…”
Section: Discussionsupporting
confidence: 92%